EFEKTIFITAS PERAN PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA (PKK) TERHADAP PEMBANGUNAN KESEHATAN MASYARAKAT DI KELURAHAN KAUMAN KECAMATAN MOJOSARI KABUPATEN MOJOKERTO - Nur Fadilah, Ayu; Muhaimin, Hikmah; Rinayuhani, Tri Ratna (MAJAPAHIT POLICY, 2023)
This research aims to determine the effectiveness of the PKK's role in community health development in Kauman Village, Apawhich are the obstacles and successes of the PKK in developing public health in Kauman Village. In getting dataTherefore, the research uses qualitative research methods, using observation, interviews and documentation.Based on Stephen P. Robbins' Organizational Theory, the results of this research explain the effectiveness of the role of the Kauman Village PKK in implementingCommunity health development programs are still less effective. It can be seen from several indicators that have not been achieved, including planning andInappropriate efficiency thereby reducing the effectiveness of the PKK's role in public health development.Lack of budget support and facilities from the village government as well as a lack of transparency regarding funding are also obstaclescommunity health development activities